Isolation and preliminary characterization of auxotrophic and morphological mutants of the yeastlike form of Paracoccidioides brasiliensis. - San Blas, F (1977)
N-methyl-N'-nitro-N-nitrosoguanidine, which is known to be a very effective mutagen in many systems, was used to induce mutants in the yeastlike form of Paracoccidioides brasiliensis strain IVIC Pb9, an imperfect fungus. Forty-three auxotrophic and 27 prototrophic morphological mutants were isolated after treatment with 50 mug of nitrosoguanidine per ml in 0.1 M citrate buffer, pH 5.0. Auxotrophic mutants required primarily either amino acids, purines, or pyrimidines. Some auxotrophs were also morphological mutants. The main morphological difference from the parental strain was the texture or the color of the yeast-like colonies. Only one prototrophic morphological mutant differed in the size and form of the yeastlike cells when compared with the parental strain. Suxotrophic mutants were used in pairwise combination to attempt heterokaryon formation without success.